Inadvertent and minimal gluten intake has a negligible role in the onset of symptoms in patients with coeliac disease on a gluten-free diet. Issue 5 (17th January 2019) - Schiepatti, Annalisa; Bellani, Valentina; Perlato, Margherita; Maimaris, Stiliano; Klersy, Catherine; Biagi, Federico
Abstract: Although the quantity of gluten that a well-instructed coeliac patient can involuntarily ingest is <10 mg of gluten/d which cannot induce significant villous damage, coeliac patients often attribute the origin of symptoms to the involuntary ingestion of trace quantities of gluten, either certain or hypothetical. Our aim was to evaluate whether the occurrence of symptoms in coeliac patients who histologically responded to a strict gluten-free diet was related to the involuntary consumption of minimal quantities of gluten. A case–control study to assess the association between gluten exposure and the occurrence of symptoms was designed. Between January 2017 and May 2018, coeliac patients attending our outpatient clinic were interviewed to detect the presence of symptoms. Based on a specifically designed form, patients were also divided into different risk groups of gluten exposure. A total of ninety-five coeliac patients on a strict gluten-free diet and with known histological recovery were enroled. Of them, fifty-two of them reported symptoms and they were enroled as cases; the remaining forty-three patients denied symptoms and were enroled as controls. Although this was not statistically significant, gluten exposure was more frequent in controls (Fisher's exact test, P =0·07). Our results show no relationship between exposure to minimal quantities of gluten and onset of symptoms in coeliac patients. Symptoms are more frequent in patients who have no risk of gluten exposure. It is possible that the presence of these symptoms leads the patients to avoid situations that may place them at risk of gluten exposure.